2019
DOI: 10.1093/mnras/stz3079
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of material around the centaur (2060) Chiron from a visible and near-infrared stellar occultation in 2011

Abstract: The centaur (2060) Chiron exhibits outgassing behaviour and possibly hosts a ring system. On 2011 November 29, Chiron occulted a fairly bright star (R~15 mag) as observed from the 3m NASA Infrared Telescope Facility (IRTF) on Mauna Kea and the 2-m Faulkes Telescope North (FTN) at Haleakala. Data were taken as visible wavelength images and simultaneous, low-resolution, near-infrared (NIR) spectra. Here, we present a detailed examination of the light-curve features in the optical data and an analysis of the NIR … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…Stellar occultations by only five centaurs -Asbolus, Bienor, Chariklo, Chiron and Echeclus-have been recorded so far (Ortiz et al 2020a), and only for three of them (Chariklo, Chiron and, very recently, Bienor -Morales et al, private communication-) multi-chord 1 occultations were obtained. A ring system around the centaur Chariklo (Braga-Ribas et al 2014) and a possible similar structure -still under discussion-around the centaur Chiron (Ortiz et al 2015;Ruprecht et al 2015;Sickafoose et al 2020) have been reported from these multi-chord occultations. This highlights the relevance of observing stellar occultations by the largest centaurs: apart from determining their sizes, shapes, albedos and other physical properties with high accuracy, detecting Orbital elements -a, q, e and i-from JPL-Horizons.…”
Section: Introductionmentioning
confidence: 73%
“…Stellar occultations by only five centaurs -Asbolus, Bienor, Chariklo, Chiron and Echeclus-have been recorded so far (Ortiz et al 2020a), and only for three of them (Chariklo, Chiron and, very recently, Bienor -Morales et al, private communication-) multi-chord 1 occultations were obtained. A ring system around the centaur Chariklo (Braga-Ribas et al 2014) and a possible similar structure -still under discussion-around the centaur Chiron (Ortiz et al 2015;Ruprecht et al 2015;Sickafoose et al 2020) have been reported from these multi-chord occultations. This highlights the relevance of observing stellar occultations by the largest centaurs: apart from determining their sizes, shapes, albedos and other physical properties with high accuracy, detecting Orbital elements -a, q, e and i-from JPL-Horizons.…”
Section: Introductionmentioning
confidence: 73%
“…During the last years, there has been a growing interest in the centaur population due to the discovery of a ring system around (10199) Chariklo (Braga-Ribas et al 2014). Also, the data of several stellar occultations by (2060) Chiron reveal features similar to those found for Chariklo; although, there is still an open debate on whether these features are attributed to rings (Ortiz et al 2015;Ruprecht et al 2015;Sickafoose et al 2020). The discovery of ring systems has opened a new branch of research to understand how these rings are formed and how they survive around these small bodies.…”
Section: Introductionmentioning
confidence: 75%
“…In contrast to the larger sawtooth shaped outbursts, the smaller symmetric outbursts may originate from a source region that spans a larger surface area on the nucleus which releases material over a longer period of time, perhaps a few days. Still another mechanism contributing to the changing brightness of Chiron is the presence of rings or ring arcs (also detected around Chariklo (Braga-Ribas et al 2014)), which changes the Centaur's apparent brightness as the aspect of the rings varies from open to edge-on (Sickafoose et al 2020;Fernández-Valenzuela 2022).…”
Section: Activity In Centaursmentioning
confidence: 98%